2017
DOI: 10.1294/jes.28.31
|View full text |Cite
|
Sign up to set email alerts
|

Does the injection of platelet-rich plasma induce changes in the gene expression and morphology of intact Thoroughbred skeletal muscle?

Abstract: Platelet-rich plasma (PRP) therapy is promising for treating skeletal muscle injuries in human athletes by promoting muscle regeneration. It might also be useful for treating muscle injuries in equine athletes. In the present study, muscle regeneration induced by injection of PRP into intact muscle of Thoroughbred was investigated. Autologous PRP and saline were injected twice into intact left and right gluteus medius muscles of seven clinically healthy Thoroughbreds. Muscle samples were collected from the inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Fukuda et al . showed that platelet-rich plasma was sufficient for growth of human BM-derived MSC [ 25 ]. We show that the use of equine platelet lysate was not a substitute for FBS as it resulted in a reduction in growth rate of EA-MSC.…”
Section: Discussionmentioning
confidence: 99%
“…Fukuda et al . showed that platelet-rich plasma was sufficient for growth of human BM-derived MSC [ 25 ]. We show that the use of equine platelet lysate was not a substitute for FBS as it resulted in a reduction in growth rate of EA-MSC.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous PRP was prepared using a double-spin method as previously described [ 8 ]. One hundred m l of equine whole blood was collected from the jugular vein of each of the 11 Thoroughbred horses using a disposable plastic syringe containing 10% sodium citrate anticoagulant (ACD-A injection, Terumo BCT Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, one study looking at uninjured skeletal muscles from racing horses showed an increase in embryonic and type I myosin heavy chain mRNA expression two and seven days after PRP injection, respectively [56]. Whether this can be translated to muscle fiber growth or hyperplasia was not examined in that particular study, and the physiological significance of this finding remains to be established.…”
Section: Recent Evidence For Platelet-based Applications To Remodel Smentioning
confidence: 98%
“…Tennis Elbow [35] Hamstring [68] Knee [47] Extensor digitorum longus [50] Ankle [27] Gastrocnemius [56] Carpal Tunnel [65] Rotator Cuff [54] Tibialis Anterior [21] [52] ▶Fig. 1 Illustration shows clinical and pre-clinical evidence for the beneficial effects of platelet-based applications on different areas of the body for tendon, ligament and skeletal muscle regeneration.…”
Section: Recent Evidence For Platelet-based Applications To Remodel Smentioning
confidence: 99%